(untitled) (American Journal of Technology and Applied Sciences, 2025)
The article presents the design of a receiver where the signal in the path can undergo detection, multi-stage processing: filtering by frequency and amplitude, amplification, frequency conversion (spectrum shift), digitalization with subsequent software processing and conversion to analog form.